An ab initio study on the structure, energetics and spectra of F(CO2)n−: the observation on the strong F–CO2 bond. (1st April 2021) - Pathak, Arup Kumar; Samanta, Alok Kumar
Abstract : Bulk VDE and SE values decrease from fluoride to iodide (F − > Cl − > Br − > I − ) in both CO2 and H2 O. Abstract : The ab initio electronic structure method, namely, second-order Møller–Plesset (MP2) perturbation theory with correlated consistent basis functions such as aug-cc-pVTZ is used to study the structures, energetics, and photoelectron spectral properties of F(CO2 ) n − ( n = 1–8) species. It is observed that one CO2 molecule forms a strong bond with the fluorine moiety in up to tetra-solvated systems, F(CO2 ) n − ( n = 1–4), and this observation is distinctly different from that of chloride, bromide, and iodide anions in the CO2 solvent. The calculated interaction energy suddenly decreases from n = 4 to n = 5 system due to the lack of strong F-CO2 bonding in F(CO2 ) n − ( n > 4) clusters. The present study indicates that the nucleophilicity of the F − ion is expected to be less when CO2 is present in H2 O in a significant proportion. The vertical detachment energy (VDE) and solvation energy (SE) values are also calculated by employing MP2 method for all systems and using CCSD(T) method for lower clusters. An excellent agreement between theory and experiment is observed for VDE and SE values (maximum error is 2%) for the mono-solvated species. Bulk VDE and SE values are also calculated by applying a microscopic theory-based expression. The VDE value of the fluoride anion is increased by 5.21 eV due to the solvation effect of CO2 and the same is enhanced by 6.66 eV due to the solvation effect of water. It is observed that in both media (CO2 and H2 O), bulk VDE and SE values are decreasing from fluoride to iodide anions i.e. F − > Cl − > Br − > I − .